2010
DOI: 10.1136/hrt.2010.198853
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of aortic valve calcification using multislice computed tomography: correlation with haemodynamic severity of aortic stenosis and clinical implication for patients with low ejection fraction

Abstract: In this large series of patients with a wide range of AS, AVC was shown to be well correlated to AVA and may be a useful adjunct for the evaluation of AS severity especially in difficult cases such as patients with low EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
176
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(202 citation statements)
references
References 28 publications
2
176
0
11
Order By: Relevance
“…AVC measurement by MDCT is a fast, simple, noninvasive, highly feasible, widely available, and highly reproducible technique. 15,16 In these studies, intraobserver and interobserver variabilities were <7%. Moreover, for visualization of calcification, CT does not require contrast and can be performed in patients with arrhythmias.…”
Section: Avc-as Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…AVC measurement by MDCT is a fast, simple, noninvasive, highly feasible, widely available, and highly reproducible technique. 15,16 In these studies, intraobserver and interobserver variabilities were <7%. Moreover, for visualization of calcification, CT does not require contrast and can be performed in patients with arrhythmias.…”
Section: Avc-as Diagnosismentioning
confidence: 99%
“…This issue can now be analyzed because cardiac computed tomography (CT) provides accurate and reproducible quantification of AVC load, 15 and multidetector CT (MDCT) may prove to be a useful adjunct tool for the evaluation of AS severity. However, previous studies suggested a single set of cutoff values for detecting severe AS regardless of sex, 16 so the impact of sex on the relation between aortic cusp calcification measured by MDCT and hemodynamic severity of AS remains uncertain. The aim of the present study was to determine the differential physiological relationship between AVC Background-Aortic valve calcification (AVC) is the intrinsic mechanism of valvular obstruction leading to aortic stenosis (AS) and is measurable by multidetector computed tomography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of calcification by MDCT strongly correlates with the hemodynamic severity of aortic stenosis by echocardiography, a useful tool in patients with low gradient severe aortic stenosis due to low left ventricular ejection fraction. [13][14][15] For the detection of severe aortic stenosis (by TTE), an aortic valve calcium threshold of .1650 arbitrary units by electron beam CT yielded a sensitivity of 82%, specificity of 80%, positive predictive value of 88%, and negative predictive value of 70%. 15 Aortic valve calcium has also been shown to be an independent predictor of mortality after adjusting for traditional risk factors and was associated with increased all-cause mortality (hazard ratio, 1.82; 95% CI 1.11-2.98).…”
Section: Aortic Stenosismentioning
confidence: 99%
“…[13][14][15] For the detection of severe aortic stenosis (by TTE), an aortic valve calcium threshold of .1650 arbitrary units by electron beam CT yielded a sensitivity of 82%, specificity of 80%, positive predictive value of 88%, and negative predictive value of 70%. 15 Aortic valve calcium has also been shown to be an independent predictor of mortality after adjusting for traditional risk factors and was associated with increased all-cause mortality (hazard ratio, 1.82; 95% CI 1.11-2.98). 16 On the basis of these data, MDCT can be considered the preferred imaging technique for both diagnosis and prognosis in patients with poor acoustic windows or left ventricular (LV) dysfunction.…”
Section: Aortic Stenosismentioning
confidence: 99%